30=-5n(6p+6)

Simple and best practice solution for 30=-5n(6p+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30=-5n(6p+6) equation:


Simplifying
30 = -5n(6p + 6)

Reorder the terms:
30 = -5n(6 + 6p)
30 = (6 * -5n + 6p * -5n)
30 = (-30n + -30np)

Solving
30 = -30n + -30np

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '30n' to each side of the equation.
30 + 30n = -30n + 30n + -30np

Combine like terms: -30n + 30n = 0
30 + 30n = 0 + -30np
30 + 30n = -30np

Add '30np' to each side of the equation.
30 + 30n + 30np = -30np + 30np

Combine like terms: -30np + 30np = 0
30 + 30n + 30np = 0

Add '-30' to each side of the equation.
30 + 30n + -30 + 30np = 0 + -30

Reorder the terms:
30 + -30 + 30n + 30np = 0 + -30

Combine like terms: 30 + -30 = 0
0 + 30n + 30np = 0 + -30
30n + 30np = 0 + -30

Combine like terms: 0 + -30 = -30
30n + 30np = -30

Reorder the terms:
30 + 30n + 30np = -30 + 30

Combine like terms: -30 + 30 = 0
30 + 30n + 30np = 0

Factor out the Greatest Common Factor (GCF), '30'.
30(1 + n + np) = 0

Ignore the factor 30.

Subproblem 1

Set the factor '(1 + n + np)' equal to zero and attempt to solve: Simplifying 1 + n + np = 0 Solving 1 + n + np = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + n + -1 + np = 0 + -1 Reorder the terms: 1 + -1 + n + np = 0 + -1 Combine like terms: 1 + -1 = 0 0 + n + np = 0 + -1 n + np = 0 + -1 Combine like terms: 0 + -1 = -1 n + np = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -5x+4-4x=76 | | -1.25x=-8+2 | | -1.25x=8+2 | | 1/5x=605 | | 1.25x=-2-8 | | 4x+2(-3x+6)=8 | | 4x-2+3x-7=51 | | 1.25x=8-2 | | y^2-12y-36=0 | | -1.25x=2+8 | | 8x+1=27x+4 | | 4x^2-x+5=x+9 | | -1.25x=8-2 | | 6(2n+2)=6(6n+3)+2 | | (4x^2)-x+5=x+9 | | -1.25x=8-6 | | -3/8y=3/16-9/16 | | -5y-9=21 | | 6(y-1)-(2y)=6 | | I/6-k=5 | | -3(t-4)+5t=4t-4 | | 2-x+-2=8 | | -.03x=400-700 | | 5b+2=c | | -.3x=400-700 | | 3n+5=25 | | -300x=400-700 | | 7x+8=3x+36 | | 8/v=3/6 | | -30x=700-400 | | 7v^2+35-42=0 | | 30=-3(a-7) |

Equations solver categories